Rare bird documentation form for Northern Goshawk at Sweet Marsh, 1983 - Moore, Francis L.et al (1983)
Rare bird documentation form for a Northern Goshawk at Sweet Marsh in Bremer County, IA on April 16, 1983. Epson - sheet feed